Teachers' perceptions of learner discipline in the intermediate phase schools of the Sikhulile Circuit : Enhlazeni Region in Mpumalanga Province - Mnisi, Phephelaphi Matilda (My University, 2021)
Recent changes in the South African education department have led to many learners’ deviant behaviour in the classroom. The abolishing of corporal punishment has accelerated lack of discipline among learners in the Ehlanzeni education region. This challenge has resulted in different perceptions among the teachers. Hence, this study aims at investigating teachers’ perceptions of learner discipline in the intermediate phase schools of the Ehlanzeni Region of Mpumalanga province. In this study, the researcher uses the mixed approach, a method which includes both quantitative and qualitative research. Data is collected through survey and semi structured interviews with principals, deputy principals, heads of departments (HOD’s) and teachers. Stratified and purposive sampling methods were used to facilitate the above process. The findings show that factors such as abolishing of corporal punishment, lack of parental involvement, lack of extramural activities and lack of clarity on policy have negatively influenced discipline in the intermediate schools. Hence, there is a need for alternative strategies to enhance the implementation of new disciplinary measures in the intermediate schools. These anomalies call for senior management or policy makers in the Department of Education (DoE) to develop relevant alternative strategies and to train teachers on policy implementation before the new disciplinary measures can be employed. This will assist teachers to prevent ill-discipline in Mpumalanga.
Thesis (M. Dev.) -- University of Limpopo, 2021
Keywords: Intermediate phase; Sikhulile circuit; Teachers and learners; Discipline; Learners’ deviant behaviour; Classroom management; Discipline